Recent developments in luteolin-loaded nanoformulations for enhanced anti-carcinogenic activities: insights from in vitro and in vivo studies - Mod Razif, Muhammad Redza Fahmi; Chan, Siok Yee; Chew, Yik Ling; Hassan, Masriana; Ahmad Hisham, Shairyzah; Abdul Rahman, Shamima; Mai, Chun Wai; Teo, Michelle Yee Mun; Kee, Phei Er; Khoo, Kuan Shiong; Lee, Siew Keah; Liew, Kai Bin (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
With approximately 18 million people affected by cancer in 2020 globally, scientists are exploring innovative approaches to develop effective treatments for various types of cancer. Traditional chemotherapy drugs, although effective against cancer cells, often lead to significant side effects on healthy tissues, such as hair loss, anemia, and nausea. To discover safer alternatives, researchers are investigating natural bioactive compounds found abundantly in plants. Luteolin, a flavonoid found in celery and artichokes, stands out due to its diverse anti-carcinogenic properties, including inhibiting proliferation, inducing apoptosis, activating autophagy, and inhibiting angiogenesis and metastasis. However, the therapeutic potential of luteolin is hindered by challenges related to its bioavailability and solubility. This critical review explores the specific anti-carcinogenic properties of luteolin while analyzing the impact of its limited bioavailability and solubility on effectiveness. Additionally, it investigates the outcomes of encapsulating luteolin in nanoformulations, providing insights into potential strategies for enhancing its anti-carcinogenic effects. Finally, the review compares the efficacy of luteolin with and without nanoformulations. This review provides valuable insights into the potential of utilizing luteolin-loaded nanoformulations as a safer and more effective method for treating cancer, contributing to the ongoing efforts in improving cancer care and outcomes worldwide.